2016
DOI: 10.5812/ircmj.21522
|View full text |Cite
|
Sign up to set email alerts
|

Iris Metastasis in a Patient With Small Cell Lung Cancer: A Case Report

Abstract: IntroductionSmall cell carcinoma constitutes the most aggressive type of lung cancer, with the greatest propensity for early disseminated disease. Although commonly neglected due to its rarity and the presence of other comorbidities, cases of iris metastasis from small cell lung cancer have been reported in the literature.Case PresentationWe present the case of a 76-year-old female. Once diagnosed, the patient already had disseminated disease with metastatic foci found in the spleen, liver, and brain. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The brain, liver, adrenal glands, and bone are among the most frequently metastasized sites of SCLC ( 13 ). Despite the high metastasis rate of SCLC, there are limited number of reports in the literature regarding iris metastases in SCLC patients ( 14 - 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The brain, liver, adrenal glands, and bone are among the most frequently metastasized sites of SCLC ( 13 ). Despite the high metastasis rate of SCLC, there are limited number of reports in the literature regarding iris metastases in SCLC patients ( 14 - 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover Delgadillo et al [17] diagnosed SCLC metastasis with excisional biopsy from the right 3 rd metatarsal bone of a 42 year old non-smoker patient. Sakellakis et al [18] reported iris metastasis of SCLC on a patient receiving chemotherapy and radiotheraphy for SCLC. Furthermore tonsillar metastasis of SCLC was mentioned on previous literatures multiple times [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The choroid is the most common site for ocular metastasis from lung cancer [3,7]. The most common site of ocular metastases from SCLC is iris [8][9][10][11][12][13][14][15][16]. One case of choroidal metastasis from SCLC was found [17].…”
Section: Discussionmentioning
confidence: 99%